THE EFFECT OF CUSTOMER EXPERIENCE AND CUSTOMER VALUE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION (STUDY ON CONSUMERS POTACORNER PASURUAN) - Karimah, Nur; Fikriah, Nur Laili (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The rising reputation of Korean culture, especially among Indonesian millennials, has generated an accelerated demand for agencies like Potacorner that cater to this unique choice. This studies aimed to analyze how customer experience and customer value impact customer loyalty through purchaser satisfaction at Potacorner. using a quantitative technique, the researchers selectively selected a pattern of a 160 members using non-probability sampling techniques. The amassed were subsequently analyzed the use of SmartPLS 3.0. The findings indicated that each client revel in and consumer cost notably prompted consumer pride. But, it changed into noted that client pride did no longer have a right away and large impact on consumer loyalty, a fashion in addition located for customer experience. In evaluation, customer price displayed a tremendous correlation with client loyalty. Moreover, the examine unveiled that purchaser satisfaction did now not act as a mediator inside the relationships among customer experience and consumer loyalty, nor among purchaser fee and customer loyalty among Potacorner Pasuruan customers. To decorate the purchaser revel in, Potacorner Pasuruan can prioritize the availability of pleasant and expert customer support, along introducing modern and diverse menu alternatives, consequently growing an enticing and fulfilling enjoy for their clients.